Réponses

2013-10-13T12:41:42+02:00
-2160
-24                90
4            -6                -15
2        2        -3        5





54
-3            -18
-1              3                      -6
1                -1             -3                2

A= 7+(-6)x(-6)
   =7+36=43
B = 13-(+3)x(-4)-8
   = 13-(-12)-8
   =13+12-8=17
C = -30+(-9+15)
   = -30+6=-24
D = -3-9x(-3)
   =-3-(-27)
   =-3+27=24
E = -3x6x(-2+8)
   = -18x(-2+8)
   =-18x6=-108
2013-10-13T13:38:44+02:00
A = 7 + (-6) x (-6)
= 7 + 36
= 43

B = 13 – (+3) x (-4) – 8
= 13 + 12 – 8 = 25 – 8
= 17

C = -30 + (-9 + 15)
= -30 + 6
= -24

D = -3  –  9 x (-3)
= -3 + 27
= 24

E = -3 x 6 x (-2 + 8)
= -18 x 6
= -108